Cognitive science and the study of the mind - Medina C., Nicolas (2008)
At present we observe a vigorous developmental of the cognitive science like a multidisciplinary field that involve several disciplines, such as cognitive psychology, artificial intelligence, linguistics, philosophy, neuroscience, and cognitive anthropology, in order to study the cognition. The study of cognition and mind has been made from a point of view of the speculative philosophy, or from perspective of the philosophy of mind, or from a point of view scientific. The hypothetical and/or theoretical proposals offered from those studies, are discussed and are submitted to experimental analysis, for the purpose to test their scientific validity. Thus, the cognitive science set the essential properties of mind and cognition, such as the representational nature of mind, the causal relation between the cognitive representation and the behavior, the symbolic nature of information mentally represented the mind like processor of information, the mind like a system of mechanisms, the modularity of mind, etc. But, at the actual cognitive science is relevant the presence of different cognitive viewpoints, on the one hand, are those that defend the classic symbolic model, on the other hand, are those that sustain the connectionist model or parallel distributed processing (PDP), and others that support mental models non representational. In conclusion, the actual study of mind and cognition is an important enterprise that involves several disciplines.